Comparing Human Subjects Research, Evidence-Based Practice, and Quality Improvement Approaches to Improve Peripheral Midline Usage in Pediatric Acute Care. - Franklin, Ashley E.; Clark, Catherine; Robinson, Isra; Wissbaum, Louise (Journal of the Association for Vascular Access)
This article compares human subjects research, evidence-based practice (EBP), and quality improvement (QI) approaches to enhance peripheral midline catheter (PML) usage in pediatric acute care. It highlights that human subjects research generates new, generalizable knowledge through controlled studies, while EBP applies this evidence to update clinical practice, and QI focuses on local, iterative improvements in care delivery. The authors describe using tabletop simulation within a pediatric teaching hospital to engage stakeholders, identify workflow barriers, and inform staff education aimed at increasing PML use, which has been shown in randomized trials to reduce device failure and complications compared to peripheral intravenous catheters. The article emphasizes the complementary roles of these paradigms and encourages vascular access professionals to collaborate with EBP mentors and employ continuous QI cycles to translate research into sustainable practice improvements that enhance patient outcomes.